Value co-creation in hotels: The views of hotel employees - Islam, M. R.; Carvalho, I.; Loureiro, S. M. C. (Brazilian Business Review, 2024)
Customer engagement in value co-creation is a key strategy to enhance company performance and strategic advantage. Although frontline employees play an important role in customer engagement - particularly in high contact services such as hotels - little research has tried to understand how employees view the value co-creation process. Hence, this study explores how hotel employees view the value co-creation process in hotels, by considering the motivations and roles of consumers and providers, and the outcomes of customer engagement in the value co-creation process. Analysis of qualitative data from an exploratory focus group with experts and context interviews with hotel employees finds mostly similarities in the way experts and employees view the value co-creation process but also some differences. Employee interviews reveal systematic attempts to engage customers in value co-creation only in high-end hotels. An overwhelming consensus is identified among participants that co-creation has a critical influence in enhancing customer experience and hotel performance.